Presidential Emergency Legislation in Indonesia: A Comparative Study of Fast-Track Mechanisms in Ecuador and Colombia - Maslul, Syaifullahil (UIN Sunan Kalijaga, 2024)
This research analyzes the presidential authority to issue Government Regulations in Lieu of Law (Perpu) during urgent conditions in Indonesia and explores the potential institutionalization of fast-track legislation as a more accountable alternative. Using statutory and conceptual approaches, the study identifies five fundamental problems with the current Perpu mechanism: disruption of legislative processes, judicial review conflicts, unlimited and subjective content scope, lack of legislative discussion, and unclear nomenclature. These issues risk executive overreach and weaken the principle of separation of powers. The research then compares Indonesia’s system with fast-track legislative mechanisms in Ecuador and Colombia. Both countries empower the president to expedite urgent bills with a 30-day legislative response period; Ecuador limits this to economic matters and grants the president authority to enact bills if the legislature fails to act, while Colombia has no such clear consequence. Based on this comparison, the study advocates abolishing the president’s authority to issue Perpu and replacing it with a formal fast-track legislative process involving the House of Representatives. This approach preserves democratic accountability, ensures legal certainty, restores separation of powers, and prevents unilateral executive actions prone to arbitrariness. The research concludes that amending Article 22 of the 1945 Constitution to institutionalize fast-track legislation offers a constitutionally sound and transparent solution to urgent legislative needs in Indonesia.